All Days 1996
DOI: 10.2118/36914-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Foam for Gas and Water Shut-off: Review of Field Experience

Abstract: Tlua paper wu prepared for~semauon aI tic I Y% SPE Europmn PeLIokumCunf.mence kld in Milm, IIIIY. 22-24 I!'w4w 1996. This paper was selecld lor presentatco by tfw SPE Program Ccmmitle.s fdwq _ C4rnfcmmaticm ccmtamed in an abslracl sumnmed by tfw author(s). Ombmts ot Iheã s presentd. fwa not km rwiewed W the SIXiaty of Petroleum Engiwws ard am Wbfectto KJlrq,h~lfw Wllhor(s) Th e material, as presented, dces nol -b rdlect any psttm o It!+ %xiety of Petroleum EIWJimeIS o, its members. Papers Fesenled al SPE meetm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…They are used in a number of industrial applications, including glass manufacturing, ore flotation, or firefighting technology [ Stevenson , ]. Enhanced oil recovery (EOR) has been the first application for subsurface environments: injection of surfactant together with gas into the subsurface has been used as early as 50 years ago [ Patzek , ] to generate foam in situ and improve oil sweep, in particular, in the framework of steam EOR [ Zhdanov et al ., ]. More recently, foams have been used to remediate aquifers contaminated with nonaqueous phase liquids (NAPLs), in a manner very similar to EOR [ Hirasaki et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…They are used in a number of industrial applications, including glass manufacturing, ore flotation, or firefighting technology [ Stevenson , ]. Enhanced oil recovery (EOR) has been the first application for subsurface environments: injection of surfactant together with gas into the subsurface has been used as early as 50 years ago [ Patzek , ] to generate foam in situ and improve oil sweep, in particular, in the framework of steam EOR [ Zhdanov et al ., ]. More recently, foams have been used to remediate aquifers contaminated with nonaqueous phase liquids (NAPLs), in a manner very similar to EOR [ Hirasaki et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The most used technique is the SAG (surfactant alternating gas) method either alone or combined with co-injection of surfactant solution and gas or with injection of pre-generated foam. Evaluation of the interpretations and results from these foam trials have shown that both positive and negative results have been achieved (Heuer and Jacobs 1968;Krause et al 1992;Aarra et al 1996;Skauge 2000, 2002;Zhdanov et al 1996;Thach et al 1996;Svorstøl et al 1997;Chukwueke et al 1998;Blaker et al 2002; testing is foam can be re-freshened with further WAG cycles after SAG. This will counteract the foam drying effect and gravity segregation that may act over time in the reservoir.…”
Section: Foam Generation Methods For Field Applicationmentioning
confidence: 99%
“…Foam is defined as a dispersion of gas in liquid (Hirasaki 1989;Kovscek and Radke 1994) and has been utilized as a tool for gas mobility-and conformance control in porous media for a wide range of applications, since the late 1950s. Industrial applications of foam in porous formations include enhanced oil recovery (EOR) (Aarra and Skauge 2000;Enick and Olsen 2012;Rossen 1996;Zhdanov et al 1996), matrix-acidizing treatments (Thompson and Gdanski 1993;Parlar et al 1995;Zeilinger et al 1995), improved underground storage of gas (Smith and Jikich 1993), as well as contaminated-aquifer remediation (Hirasaki et al 1997). Despite its unique properties, broad applicability and extensive experience gained over the past 60 years, foam has not become a standard reservoir engineering oil recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed in the paper were used when planning and implementing the program of non-stationary flooding at the first production facility of the seventh block (central part) at the deposit of Severnye Buzachi [3].…”
Section: Methodsmentioning
confidence: 99%